Bacillus-based biocontrol beyond chemical control in central Africa: the challenge of turning myth into reality - Nihorimbere, Gaspard; Korangi Alleluya, Virginie; Nimbeshaho, François; Nihorimbere, Venant; Legrève, Anne; Ongena, Marc (Frontiers in Plant Science, 2024)
Agricultural productivity in the Great Lakes Countries of Central Africa, including Burundi, Rwanda, and the Democratic Republic of Congo, is affected by a wide range of diseases and pests which are mainly controlled by chemical pesticides. However, more than 30% of the pesticides used in the region are banned in European Union due to their high toxicity. Globally available safe and ecofriendly biological alternatives to chemicals are virtually non-existent in the region. Bacillus PGPRbased biocontrol products are the most dominant in the market and have proven their efficacy in controlling major plant diseases reported in the region. With this review, we present the current situation of disease and pest management and urges the need to utilize Bacillus-based control as a possible sustainable alternative to chemical pesticides. A repertoire of strains from the Bacillus subtilis group that have shown great potential to antagonize local pathogens is provided, and efforts to promote their use, as well as the search for indigenous and more adapted Bacillus strains to local agro-ecological conditions, should be undertaken to make sustainable agriculture a reality in the region.